The Reciprocal Relationship Between Quiet Quitting and Turnover Intention Among Marketing Employees: Critical Insights from Cross-Lagged Path Analysis - Theophilus Ehidiamen Oamen (TALENTA Publisher, Universitas Sumatera Utara, 2026)
Quiet Quitting (QQ) and Turnover Intentions (TI) are emerging contemporary human resource issues that influence employee behavior and their decision to stay or leave an organization. QQ and TI pose potential threats to long-term employee retention, sustained productivity, and workplace continuity. Research on QQ and TI has mainly been cross-sectional, with limited empirical evidence from longitudinal data on how employee QQ and TI evolve and interrelate over time. Additionally, the literature has yet to reach a consensus on which variable predicts the other. To address these gaps, based on withdrawal cognition theory, job embeddedness theory, conservation of resources theory, the progressive withdrawal theory, and Herzberg’s Hygiene-Motivation theory, cross-lagged path modeling was used to test six proposed hypotheses. Survey questionnaires collected data from marketing professionals in two waves—initially at Time 1 (N = 102) and a follow-up at Time 2 (N = 81), seven months later. Hypothesis testing was conducted using covariance-based structural equation modeling. Results showed a positive, significant correlational association between QQ and TI at each time point, indicating that increases in one are associated with increases in the other. TI remained stable or consistent from Time 1 to Time 2, while QQ showed lower and non-significant stability. TI was a positive causal temporal predictor of QQ, not vice-versa. Based on strong theoretical foundations, the study examined the ongoing debate of the temporal reciprocal effects of QQ and TI from a longitudinal perspective among marketing employees. The contribution to both theory and practice was summarized.